The Influence of Direct Reading Thinking Activity (DRTA) Strategy andReading Interest toward Reading Achievement of the Tenth Grade Students at MA Miftahul Jannah Peninjauan OKU - Miftahul Jannah; Indawan Syahri; Mulyadi Mulyadi (ELTE Journal (English Languange Teaching and Education), 2018)
AbstractThe aim of this study was to find out whether or not there was a significant interaction effect of DRTA strategy and reading interest on reading achievement before and after being taught using DRTA Strategy and conventional strategy. The samples of the studywere sixty students of the tenth grade of MA Miftahul Jannah in academic year 2017/2018. The samples of the study were the 15 students’ high interest and 15 students’ low interest in experimental group and there were 15 students’ high interest and 15 students’ low interest in conventional strategy. Two group pre-test post-test experimental and control group designs were used. Reading comprehension test was used to know the students’ reading achievement. The groups were given a treatment for eight meeting and were checked for comprehension achievement through a readingtest. The data were analyzed by using paired sample t-test in SPSS version 17.0. The results showed that there is a significant interaction effect of DRTA strategy and reading interest on reading acievment before and after being taught using DRTA Strategy and conventional strategy. If there was p-value less than or equal to 0.05, then it was assumed that there was a significant interaction, it could be seen that Fobtained was 950,882 with the p-value 0,032. Since the p-value was lower than 0.05, it meant that was a significant interaction effect or strategies used DRTA Strategy and reading interest toward reading achievement.Key words: DRTA (direct reading thinking activity) strategy, reading interest, reading achievement